The Implementation of a Collaborative Pediatric Telesimulation Intervention in Rural Critical Access Hospitals. Issue 3 (31st January 2021) - Auerbach, Marc; Patterson, Mary; Mills, William A; Katznelson, Jessica
Abstract: Background: Over 5.8 million pediatric visits to rural emergency department (EDs) occur each year in the United States. Most rural EDs care for less than five pediatric patients per day and are not well prepared for pediatrics. Simulation has been associated with improvements in pediatric preparedness. The implementation of pediatric simulation in rural settings is challenging due to limited access to equipment and pediatric specialists. Telesimulation involves a remote facilitator interacting with onsite learners. This article aims to describe the implementation experiences and participant feedback of a 1‐year remotely facilitated pediatric emergency telesimulation program in three critical‐access hospitals. Methods: Three hospitals were recruited to participate with a nurse manager serving as the on‐site lead. The managers worked with a study investigator to set up the simulation technology during an in‐person pilot testing visit with the off‐site facilitators. A curriculum consisting of eight pediatric telesimulations and debriefings was conducted over a 12‐month period. Participant feedback was collected via a paper survey after each simulation. Implementation metrics were collected after each session including technical and logistic issues. Results: Of 147 participant feedback surveys 90% reported that pediatric simulations should be conducted on a regular basis and overall feedback was positive. Forty‐seven of 48 simulations were completed on the first attempt with few major technologic issues. The most common issue encountered related to the simulator not working correctly locally and involved the facilitator running the session without the heart and lung sounds. All debriefings occurred without any issues. Conclusions: This replicable telesimulation program can be used in the small, rural hospital setting, overcoming time and distance barriers and lending pediatric emergency medicine expertise to the education of critical‐access hospital providers.